Klasifikasi Biaya Lingkungan pada Rumah Sakit Jember Klinik - Muhammad Ridwan; Septarina Prita D. S; S. Sudarno (UPT Penerbitan Universitas Jember, 2019)
This study aims to determine the classification of environmental costs at Jember Klinik Hospital and to know whether there are differences in environmental cost classification made by Jember Klinik Hospital with Environment Related Cost Categories of EMA. This research type is qualitative research with descriptive method. Data collection techniques used interview, documentation and obsevation. Test the validity of data in this study using data triangulation . Based on the research, it is concluded that Jember Klinik Hospital classifies environmental costs in accordance with the Decree of the Minister of Health of the Republic of Indonesia No. 1204 / MENKES / SK / X / 2004 on Hospital Health Requirements and the environmental cost classification of Jember Klinik Hospital has been in accordance with the ERCC of EMA classification but the cost of research and development is still not implemented by the Jember Klinik Hospital some have been appropriate. Keywords: Cost Classification, Environmental Cost, Hospital, and ERCC of EMA